Effects of Menstrual Self-management Education Program on Knowledge and Behavior of Menstrual Self-management in High School Girls - Jeonghye Min; Sukhee Ahn (Korean Society of Women Health Nursing, 2018)
PURPOSE: To examine the effect of menstrual self-management education program on knowledge and behavior of menstrual self-management in high school girls. METHODS: With a randomized controlled trial, 100 high school girl students were randomly assigned into experimental group and control group. Menstruation self-management program was consisted of a total of four sessions of education program (1 hour of education per session). Control group only received the first class of education. Measurement tools were 20-item menstrual knowledge scale and 12-item women's genito-urinary hygiene scale. Pretest and post-test questionnaires were administered. RESULTS: There were significant differences in menstrual knowledge as well as menstrual self-management behavior between the two groups. The experimental group showed significant improvement in both menstrual knowledge score (t=13.37, p < .001) and menstrual self-management behavior score (t=8.38, p < .001) than the control group. CONCLUSION: Results of this study suggest that the monthly self-management education program is effective in increasing the knowledge of menstruation of female high school students and enhancing their performance. This program needs to be implemented as a part of high school's standard sex education. Further study is needed to analyze follow-up effects of the program on self-management behavior of students after at least one menstrual cycle.